Planning for Replacement of GI Endoscopy Equipment in a Regional Setting - Samiee, Maryam; Wiebe, Shawn; Gaamangwe, Tidimogo (CMBES Proceedings, 2016)
The management of endoscopic equipment is commonly facilitated under a comprehensive equipment/consumable service contract. Contract can present challenges at renewal/termination time. Analysis of status and implications of different replacement options is necessary. This paper presents the results of our investigation into the status of endoscopy equipment in preparation for end of contract. The different options that were analyzed will be presented and provide a learning opportunity for other Clinical Engineering programs. An environmental scan of endoscopes and ancillary equipment within the Winnipeg Regional Health Authority facilities was conducted. The scan involved consultation with site equipment managers, manufacturers and third party repair companies. This information was reconciled with inventory in the hospital databases. The collected information was analyzed through various statistical parameters to delineate the various dimensions regarding distribution, status and impact of different replacement models/scenarios. The results of the scan provided an important insight into the current practice of endoscope management as well as the clinical, technical and economic impact of a possible vendor change. Inter-departmental equipment sharing was one of the aspects to consider. Technical implications included propriety equipment connections, which may necessitate complete replacement; approximately 70% worth of endoscopic equipment. The results provided invaluable input to inform an RFP preparation. An environmental scan is an important prerequisite for an evidence-informed replacement plan. This study considered some of the most relevant factors and provided invaluable information for stakeholders to prepare a comprehensive RFP. The study provides a learning opportunity for other CE programs in a similar situation.